The effects of negative life events on college students’ problematic online gaming use: a chain-mediated model of boredom proneness regulation - Zhao, Zhenyu; Zhao, Mengmeng; Wang, Ruixin; Pan, Huiru; Li, Lina; Luo, Hongge (Frontiers in Psychology, 2024)
The study investigated the impact of negative life events on college students' problematic online gaming use, as well as the mediating role of basic psychological needs and anxiety, and the moderating effect of boredom proneness. A total of 1102 college students were surveyed by using the Adolescent Negative Life Events Scale, Basic Psychological Needs Scale, GAD-7, DSM-5, and Boredom Proneness Scale. From the sample, 881 participants with experience in online gaming were selected for the study. The results showed that: (1) Controlling for gender and grade, negative life events significantly and positively predicted problematic online gaming use. (2) Basic psychological needs and anxiety played a mediating role in the relationship between negative life events and problematic online gaming use. (3) Boredom proneness significantly moderated the first half of the model. Basic psychological needs and anxiety mediate the relationship between negative life events and college students' problematic online gaming use. Moreover, under conditions of low boredom proneness, the independent mediating effect of basic psychological needs and the mediating effect of basic psychological needs and anxiety are enhanced, while the independent mediating effect of anxiety is weakened.